Standardisation of 54Mn and 65Zn using a software coincidence counting system - Havelka, Miroslav; Auerbach, Pavel; Sochorová, Jana (Applied radiation and isotopes, 2006)
The activities of 54Mn and 65Zn have been determined by 4pi(PC)-gamma coincidence counting, with efficiency variation performed by the conventional method of altering the self-absorption in the sources as well as by the computer discrimination method. The standardisation of 65Zn presents some complications requiring optimisation of the gamma-ray energy window settings to achieve a linear efficiency-extrapolation curve. Determination of these optimal settings by the conventional coincidence method is a tedious task. These difficulties have been reduced by the utilisation of a software coincidence counting system that records time and amplitude information of individual pulses from coincidence measurements, where the coincidence parameters are set after the data collection process has completed, facilitating multiple data evaluations on a single data set. The optimal gamma-ray energy window settings for the 65Zn standardisation were derived from the results of the 54Mn standardisation, as well as from studies of the 65Zn data itself. The setting of the PC channel thresholds for K and both (K+L) electrons is also discussed. The results are compared with those attained using conventional coincidence counting.
Keywords: mangan; Radiation Dosage; Software; Zinc Radioisotopes; Reference Standards; radioizotopy zinku; reprodukovatelnost výsledků; spektrometrie gama; Czech Republic; Sensitivity and Specificity; Algorithms; scintilace - počítání; Spectrometry, Gamma; Radioisotopes; Česká republika; software; Scintillation Counting; referenční hodnoty; Guidelines as Topic; Manganese; referenční standardy; směrnice jako téma; senzitivita a specificita; Reproducibility of Results; radionuklidy; Reference Values; dávka záření; algoritmy